Pola Asuh Demokratis dan Kecerdasan Emosional dengan Prestasi Belajar Siswa-Siswi SMP Bilingual - Rahayu, Sesanti; Hendrati, Fabiola (Persona:Jurnal Psikologi Indonesia, 2015)
This study aimed to analyze the relationship tendency democraticparenting and emotional intelligence and academic achievement Bilingual juniorstudents. Subject reaserch are 124 male and female students grade 7 juniorBilingual tepadu Junwangi-Krian. The implementation of data collection is done injunior high school student and Bilingual Integrated. Distributed measurement scaleconsists of two questionnaires: 1) Democracy parenting scale, 2) emotionalintelligence scale. The result show F regression = 2.898 de-ngan p = 0.059 (p>0.05) , this means that there is no significant relationship between democraticparenting and emotional maturity with Academic Achievement.Keywords : learning achievement, parenting Democracy, emotional intelligence